2021
DOI: 10.5603/cj.a2020.0181
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital outcomes of mechanical complications in acute myocardial infarction: Analysis from a nationwide Spanish database

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 27 publications
(34 reference statements)
1
7
0
11
Order By: Relevance
“…In a United States observational analysis of >9 million hospitalizations spanning from 2003-2015, the rates of mechanical complications were approximately 0.27% among patients with ST-elevation myocardial infarction (STEMI) and 0.06% among patients with non-ST-elevation myocardial infarction (NSTEMI), without any observed declines in secular trends (4). Similar findings were observed in an analysis from the Spanish National Health System between 2010-2015 which showed that the prevalence of post-MI mechanical complications was 0.35% (5). Among the various post-AMI mechanical complications, VSR remains the most common complication with an estimated prevalence of 0.17% to 0.91%, while the prevalence of PMR and FWR are ~0.05% to 0.26% and 0.01% to 0.52%, respectively (6).…”
supporting
confidence: 83%
See 1 more Smart Citation
“…In a United States observational analysis of >9 million hospitalizations spanning from 2003-2015, the rates of mechanical complications were approximately 0.27% among patients with ST-elevation myocardial infarction (STEMI) and 0.06% among patients with non-ST-elevation myocardial infarction (NSTEMI), without any observed declines in secular trends (4). Similar findings were observed in an analysis from the Spanish National Health System between 2010-2015 which showed that the prevalence of post-MI mechanical complications was 0.35% (5). Among the various post-AMI mechanical complications, VSR remains the most common complication with an estimated prevalence of 0.17% to 0.91%, while the prevalence of PMR and FWR are ~0.05% to 0.26% and 0.01% to 0.52%, respectively (6).…”
supporting
confidence: 83%
“…Despite advances in pharmacological management of AMI patients and use of mechanical circulatory support devices among patients with cardiogenic shock, inhospital mortality rates among patients with mechanical complications has remained significantly high (~40-50%) and has not declined over the past 2 decades (4,8,9). While factors such as advanced age, female sex, STEMI presentation, TIMI 0 or I flow, cardiogenic shock, and cardio-respiratory failure are linked with higher in-hospital mortality (4,8), centers with cardiac intensive care units and greater experience seem to have better outcomes (5). Importantly, some observational studies have suggested that surgical repair is associated with improved in-hospital mortality (2,4).…”
mentioning
confidence: 99%
“…Furthermore, studies assessing the temporal trends following myocardial infarction show a reduction in the rates of mechanical complications over the years. However, when these events occur, they continue to be associated with high mortality rates, which have not improved over the years (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that most VSD occurs 3-5 days after AMI [3] . The patients receiving drug therapy alone have a median survival time of 5 days; more than 75% of patients die within 12 days after the onset of VSD symptoms, with 93.6% of 30-day mortality rate, and 96.2% of long-term mortality rate [4] . Therefore, based on the experience, the patient's onset of VSD might be approximately 4 weeks before the first visit.…”
Section: Discussionmentioning
confidence: 99%